PEMANFAATAN ARANG SABUT KELAPA DAN KULIT PINANG MENJADI BIOBRIKET UNTUK MENINGKATKAN NILAI TAMBAH - Arisandi, Meri; Yulia, Ade; Prihantoro, Rudi; Fiardilla, Fauziah (PPPM POLTESA, 2023)
Areca nut coir contains several chemical compounds, i.e., cellulose (34,18%), hemicellulose (20.83%), and lignin (31.6%). These chemical compounds are a source of carbon in the manufacture of activated charcoal or adsorbents and coconut coir is a material containing lignicellulose which can be used as a substitute for fuel. One way to use areca nut and coconut coir is to make biobriquettes. Processing of areca and coconut coir into biobriquettes deals with numerous production factors, starting from additional materials, labor, production equipment, and other materials. Processing costs are conducted to obtain higher prices and higher profits than without a production process, so value added analysis is needed. The purpose of this research is to find out the added value generated from processing areca nut shells and coconut coir into biobriquettes. Data were obtained from primary and secondary data. The methods used in this research are descriptive and quantitative methods. Based on the results of the research, processing of areca shell charcoal and coconut coir into biobriquettes starts from ordering raw materials, maintenance and storage of raw materials. The production process is conducted by weighing the raw materials, carbonizing, milling, sieving, mixing charcoal flour with tapioca flour, moulding, drying and packaging. and added value analysis shows that the business plan for processing areca shell charcoal and coconut coir into biobriquettes obtains an added value of Rp. 3,077/kg of raw materials. A large added value of zero (Rp. 3,077> 0) means that the utilization of areca nut shells and coconut husks into biobriquettes generates added value.